An Analysis Upon Limitations to Low Achievers’ Achievement In the Elementary Classroom As Observed By Teachers: Exploring limitations to success for low achievers in elementary classrooms (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The purpose of this study was to explore the limitationsto success that children who have low achievement encounter in the elementaryclassroom as perceived by elementary school teachers. Educational systembarriers include a lack of appropriate teacher training, a fast pacedcurriculum, the use of high stakes tests, inadequate school staffing and a lackof policy maker understanding of the academic needs of children with lowachievement. In addition, participants indicated that children with lowachievement tend to have low self-esteem, a need for extra educational time andattention and a need for specific learning strategies such as hands-on andexperiential learning.